A Case of Progressive Stroke on Posterior Circulation with Transient Bilateral Oculomotor Palsy - Chiaki Takahashi (Case Reports in Neurological Medicine)
Infarction located in the midbrain and pons presents various ophthalmic symptoms, because of the damage of the nuclei that control the movement of internal and external ocular and palpebral muscles. We experienced a case which presented with rare ocular symptoms and course. A 61-year-old man presented with left hemiparesis and dysarthria, bilateral ptosis, and bilateral impaired eyeball movement: right eyeball movement was totally impaired and left could only perform slight adduction. MRI showed fresh stroke in the right thalamus, cerebral crus, and posterior lobe and cuneate lesion on bilateral paramedian portion of the midbrain. MRA showed occlusion in the P1 area of the posterior cerebral artery (PCA). Transesophageal echocardiography (TEE) showed findings of a patent foramen ovale (PFO). These findings suggested cardioembolic stroke as a cause of PCA occlusion and we prescribed rivaroxaban. The patient’s eyeball and eyelid movement, only on the left side, was improved imperfectly 2 weeks later. We thought that neurological findings and course of this case may have arisen from dysfunction of the oculomotor nucleus and oculomotor fascicles, and MLF results from the presence of the lesion in paramedian midbrain and pons.